2002
DOI: 10.1046/j.1440-6047.2002.00268.x
|View full text |Cite
|
Sign up to set email alerts
|

Ocular manifestation of vitamin A deficiency among Orang Asli (Aborigine) children in Malaysia

Abstract: This study determined the prevalence of ocular manifestation of vitamin A deficiency in Orang Asli (Aborigine) children. Night blindness was found in 16.0% of the children, conjunctiva xerosis in 57.3%, Bitot's spot in 2.8%, corneal xerosis in 0.5% and corneal scars in 5.6%. These findings show that history of night blindness had sensitivity, specificity and predictive value (positive) of 47.2, 98.1 and 96.2%, respectively, compared with the standard diagnosis procedure using luxometer readings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…[24] However, a study by Ngah et al , conducted on children for ocular manifestations of vitamin A deficiency, revealed that night blindness was present in overall 16% of the children, conjunctival xerosis in 57%, Bitot's spots in 3%, corneal xerosis in 0.5%, and corneal scar in 6%; and overall 82% of the children had eye manifestation of vitamin A deficiency. [25] This study shows that night blindness was significantly associated with low RBP levels. There was a 100% sensitivity of low serum RBP levels and the diagnosis of ocular manifestations; however, four patients with normal RBP levels had ocular manifestations.…”
Section: Discussionmentioning
confidence: 85%
“…[24] However, a study by Ngah et al , conducted on children for ocular manifestations of vitamin A deficiency, revealed that night blindness was present in overall 16% of the children, conjunctival xerosis in 57%, Bitot's spots in 3%, corneal xerosis in 0.5%, and corneal scar in 6%; and overall 82% of the children had eye manifestation of vitamin A deficiency. [25] This study shows that night blindness was significantly associated with low RBP levels. There was a 100% sensitivity of low serum RBP levels and the diagnosis of ocular manifestations; however, four patients with normal RBP levels had ocular manifestations.…”
Section: Discussionmentioning
confidence: 85%
“…These findings were consistent with those of previous local studies conducted among Aboriginal children. 16,26 In comparison with the neighboring countries in Southeast Asia, a higher prevalence of VAD (serum retinol concentration < 0.70 μmol/L) was reported among children in rural regions of southern Vietnam and along the southern coast of central Java in Indonesia. 10,27 During the 1990s, Indonesia showed good progress in reducing VAD but the prevalence of the transition changed after the tsunami disaster of 2004 that killed more than 200,000 persons in the territories of Ache, Nias, and Sumatra.…”
Section: Discussionmentioning
confidence: 99%
“…When serum retinol concentrations fall below 1.0 µmol/L, impaired adaptation to the dark can begin, although it is more common when they fall below 0.7 µmol/L [ 4 ]. Many studies have employed a history of night blindness given by parents as part of the method for assessing the prevalence of this condition [ 18 , 19 ]. Both our patients were intellectually disabled, which hinders the ability of parents to notice the sign.…”
Section: Discussionmentioning
confidence: 99%